(untitled) (Indian Journal of Public Health Research & Development, 2024)
Background : Hospital housekeeping workers (HHW), also known as hospital janitorial staff, are individuals responsible for maintaining the cleanliness and hygiene of hospital facilities. This study focuses on the perceptions of HIV/AIDS among HHWs and their role in controlling its spread. The aims included assessing their knowledge of HIV/AIDS transmission, reducing stigma, and evaluating the impact of Information, Education, and Communication (IEC) on their awareness and perception. Methods : Conducted at a Chennai tertiary care hospital from December 2022 to January 2023, this interventional study involved 25 HHWs. The research utilised a structured questionnaire for socio-demographic details and HIV/AIDS-related questions, implementing pre- and post-tests after health education. Statistical analysis was performed using IBM SPSS Statistics v20.0. The chi-square test was used to arrive at a p-value to test the significance between pre- and post-intervention test results. A p-value of <0.05 was considered statistically significant. Conclusion : Post-intervention, the knowledge that using condoms reduces transmission very significantly increased to 100% (p-value=<0.0000001), awareness that HIV/AIDS doesn’t transmit through touch very significantly improved to 88% (p-value=<0.0000001), belief in hope for affected individuals rose very significantly to 96% (p-value=<0.0000001) and understanding that mosquito bites don’t cause transmission very significantly increased to 88% (p-value=<0.0000001). These findings emphasis the positive impact of health-education on HHWs. Empowering HHWs with the necessary knowledge to address fear-based stigma and boosting awareness is pivotal. Conducting effective and periodic awareness programs significantly enhances HHWs’ understanding of HIV/AIDS, and is a crucial step in eliminating occupational transmissions and stigma.